Personnel Perception of Continued Relevance of Shorthand and Typewriting Skills to Office Management in Osun State Owned Tertiary Institutions, Nigeria. - Oguntimehin, Y. Abiodun; Oludele, Yemisi I. (NIU Journal of Humanities; Vol 3 No No. 2 (2018): KIU Journal of Humanities, Vol. 3 No. 2, June 2018, 2018)
Shorthand and Typewriting are two major skilled courses in Office Education Programme in tertiary institutions in Nigeria. Acquisitions of skills in these two subjects were regarded as trade-in-stock for secretarial practitioners in managing offices. But with the current applications of Information and Communication Technology to manage in offices, the relevance of Typewriting and Shorthand skills became a subject of discourse. The main objective was to determine the continued relevance of the two subjectâ€™s skills to office management in Osun State owned tertiary institutions. The study adopted a descriptive survey design. Five research questions and five hypotheses were raised for the study. The population comprised 171 executives with their individual secretaries, making 342 participants. The entire population was used as the sample size. Structured questionnaire was used to collect data and descriptive statistics to analyse. The findings among others revealed that Shorthand and Typewriting were still relevant to office management. Based on the findings, it is recommended that secretarial training institutions should intensify efforts towards the training of students in these â€œtwinâ€ subjects. Keywords: Personnel, Continued Relevance, Shorthand Skill, Typewriting Skills and Office Management.